Causes of changes in carotid intima-media thickness: a literature review. Issue 1 (December 2015) - Qu, Baoge; Qu, Tao
Abstract Atherosclerosis causes significant morbidity and mortality. Carotid intima-media thickness (CIMT) predicts future cardiovascular and ischaemic stroke incidence. CIMT, a measure of atherosclerotic disease, can be reliably determined in vivo by carotid ultrasound. In this review, we determined that CIMT is associated with traditional cardiovascular risk factors such as age, sex, race, smoking, alcohol consumption, habitual endurance exercise, blood pressure, dyslipidemia, dietary patterns, risk-lowering drug therapy, glycemia, hyperuricemia, obesity-related anthropometric parameters, obesity and obesity-related diseases. We also found that CIMT is associated with novel risk factors, including heredity, certain genotypic indices, anthropometric cardiovascular parameters, rheumatoid arthritis, immunological diseases, inflammatory cytokines, lipid peroxidation, anthropometric hemocyte parameters, infectious diseases, vitamin D, matrix metalloproteinases, and other novel factors and diseases. However, the conclusions are inconsonant; the underlying causes of these associations remain to be further explored.